Standardising definitions for the pre-eclampsia core outcome set: A consensus development study - Duffy, James M.N.; Cairns, Alexandra E.; Magee, Laura A.; von Dadelszen, Peter; van 't Hooft, Janneke; Gale, Chris; Brown, Mark; Chappell, Lucy C.; Grobman, William A.; Fitzpatrick, Ray; Karumanchi, S. Ananth; Lucas, D. Nuala; et al. (Elsevier, 2020)
Objectives: To develop consensus definitions for the core outcome set for pre-eclampsia. Study design: Potential definitions for individual core outcomes were identified across four formal definition development initiatives, nine national and international guidelines, 12 Cochrane systematic reviews, and 79 randomised trials. Eighty-six definitions were entered into the consensus development meeting. Ten healthcare professionals and three researchers, including six participants who had experience of conducting research in low- and middle-income countries, participated in the consensus development process. The final core outcome set was approved by an international steering group. Results: Consensus definitions were developed for all core outcomes. When considering stroke, pulmonary oedema, acute kidney injury, raised liver enzymes, low platelets, birth weight, and neonatal seizures, consensus definitions were developed specifically for low- and middle-income countries because of the limited availability of diagnostic interventions including computerised tomography, chest x-ray, laboratory tests, equipment, and electroencephalogram monitoring. Conclusions: Consensus on measurements for the pre-eclampsia core outcome set will help to ensure consistency across future randomised trials and systematic reviews. Such standardization should make research evidence more accessible and facilitate the translation of research into clinical practice. Video abstract can be available at: www.dropbox.com/s/ftrgvrfu0u9glqd/6.%20Standardising%20definitions%20in%20teh%20pre-eclampsia%20core%20outcome%20set%3A%20a%20consensus%20development%20study.mp4?dl=0.
Keywords: Consensus development study; Core outcome set; Hypertension in pregnancy; Outcome measure; Pre-eclampsia; Randomised controlled trials